Failure assessment and prevention for interacting crack problems in offshore pipelines - Sun, Hong Bin (Nanyang Technological University, 2022)
The petroleum industries had been investing millions over dollar in maintaining offshore pipe Lines due to its key part in deliver oil and gas for our daily needs. One of the most general Material use in building a economical offshore pipe line is carbon steel. these pipelines are build by connecting many shorter pipes together by a welding process. during the welding process, defects or micro cracks is inevitably generated due to bending stress. These micro cracks will gradually grow larger and propagate towards each other under the cyclic loading . In addition, the salt environment under sea will Act as catalyst to speed up the cracking. These factors will shorten the life span Of the pipeline material and eventually lead to failure of pipes due to rapture. In the present reports. The theory of Finite element method is applied to simulate the fatigue behavior of multiple 3 dimensional semi-elliptical cracks under a cyclic tensile force by using ANSYS Workbench 19.2. Fatigue crack growth rate has been investigated by analyzing stress intensity factor (SIF) values and related parameters from numerical results of simulation. The separation length between two cracks are the major variables, and the influence of the change on cracks separation distance has been studied and discussed.